Pengembangan instrumen keterampilan dasar konseling Pada mahasiswa calon konselor - Tri Anjar (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
This research aims to develop basic skills counseling instruments which refer to various counseling theories and techniques that will be used to measure the ability of students in individual counseling practicum courses. Subjects were students Prodi BK sixth semester, the University of Muhammadiyah Metro totaling 44 students. Retrieving data using Likert scale model of the scale of basic counseling skills. The analysis revealed the acquisition of scores of each indicator that is the understanding of theoretical concepts and techniques of counseling the ideal score is 616, while perolehen a total score of 382, the indicator Already using theoretical approach and counseling techniques ideal score is 264, while the acquisition of the total score is 166, then the accuracy of selecting an approach to counseling theories and techniques, the ideal score is 264 and earned a total score of 144, and the indicators used counseling theories and techniques correctly, obtained a total score of 383 out of a score of 616 is ideal. Conclusion of research is the basis of student counseling keterampilaan Prodi BK sixth semester at the University of Muhammadiyah Metro, is still relatively moderate. Recommendations advice pembeajaran quality needs to be improved and need to be arranged individual counseling practicum guides more specific and easier to use prospective student counselor.